Anionically functionalized guar gum embedded with silica nanoparticles: An efficient nanocomposite adsorbent for rapid adsorptive removal of toxic cationic dyes and metal ions. (February 2017) - Patra, Abhay Shankar; Ghorai, Soumitra; Sarkar, Debabrata; Das, Raghunath; Sarkar, Supriya; Pal, Sagar
Graphical abstract: Highlights: h-GG/SiO2 nanocomposite has been synthesized through sol-gel technique. The nanocomposite is an efficient adsorbent for removal of toxic dyes/metal ions. The nanocomposite based adsorbent showed good recyclability. Abstract: In the present work, a novel biodegradable nanocomposite has been developed (h-GG/SiO2 ) based on anionically modified guar gum and in-situ deposited SiO2 NPs through sol-gel technique. Here the anionically modified guar gum stimulates the silica polymerization process and hence acts as a unique template for the development of spherical SiO2 NPs. Batch adsorption studies indicate that h-GG/SiO2 nanocomposite shows remarkable adsorption capacity for cationic dyes/metal ions (Qmax : 781.25 mg g −1 for malachite green (MG), 281.69 mg g −1 for safranin (SF); 645.16 mg g −1 for Pb 2+, 709.21 mg g −1 for Cd 2+ ) as well as it efficiently and selectively removes cationic MG from mixture of dye solutions. Finally the worthy regenerative efficacy of h-GG/SiO2 facilitates the adsorbent to be economically promising for practical application in the field of wastewater management.